Synthesis of the C‐8–C‐24 Fragment of Maltepolide C by Using a Tandem Dihydroxylation/SN2 Cyclization Sequence. Issue 23 (2nd July 2015) - Mohapatra, Debendra K.; Reddy, D. Sai; Reddy, G. Sudhakar; Yadav, Jhillu S.
Abstract: A highly stereoselective synthesis of the C‐8–C‐24 fragment of maltepolide C has been achieved in a convergent and efficient manner by utilizing a tandem Sharpless asymmetric dihydroxylation (SAD)/SN 2 cyclization reaction sequence as the key step. Other important steps include a Crimmins‐modified Evans aldol reaction, a Brown asymmetric allylation, a Horner–Wadsworth–Emmons olefination, and a Corey–Bakshi–Shibata (CBS) reduction. Abstract : A highly stereoselective synthesis of the C‐8–C‐24 fragment of maltepolide C has been achieved in a convergent and efficient manner by utilizing a tandem Sharpless asymmetric dihydroxylation (SAD)/SN 2 cyclization reaction sequence as the key step.